Yeast Models for the Study of Amyloid-Associated Disorders and Development of Future Therapy - Rencus-Lazar, Sigal; DeRowe, Yasmin; Adsi, Hanaa; Gazit, Ehud; Laor, Dana (Frontiers in Molecular Biosciences, 2019)
First described almost two decades ago, the pioneering yeast models of neurodegenerative disorders, including Alzheimer’s, Parkinson’s and Huntington’s diseases, have become well-established research tools, providing both basic mechanistic insights as well as a platform for the development of therapeutic agents. These maladies are associated with the formation of aggregative amyloid protein structures showing common characteristics, such as the assembly of soluble oligomeric species, binding of indicative dyes, and apoptotic cytotoxicity. The canonical yeast models have recently been expanded by the establishment of a model for type II diabetes, a non-neurological amyloid-associated disease. While these model systems require the exogenous expression of mammalian proteins in yeast, an additional amyloid-associated disease model, comprising solely mutations of endogenous yeast genes, has been recently described. Mutated in the adenine salvage pathway, this yeast model exhibits adenine accumulation, thereby recapitulating adenine inborn error of metabolism disorders. Moreover, in line with the recent extension of the amyloid hypothesis to include metabolite amyloids, in addition to protein-associated ones, the intracellular assembly of adenine amyloid-like structures has been demonstrated using this yeast model. In this review, we describe currently available yeast models of diverse amyloid-associated disorders, as well as their impact on our understanding of disease mechanisms and contribution to future potential drug development.